Prenatal care assessment according to the Prenatal and Birth Humanization Program - Maria Alice Tsunechiro; Marlise de Oliveira Pimentel Lima; Isabel Cristina Bonadio; Marianne Dias Corrêa; Amanda Villalba Alves da Silva; Suzana Cristina Teixeira Donato
Abstract Objectives: to analyze prenatal care process in primary health care units and compare the prenatal adequacy in the third trimester with maternal and perinatal outcomes. Methods: a cross-sectional study of 2,404 pregnant women assisted in 2011in twelve primary health care units in the South region of São Paulo city. The data was collected through medical records. The assessment was based on the indicators process of the Programa de Humanização do Pré-natal e Nascimento (PHPN) (Prenatal and Birth Humanization Program). The prenatal adequacy in the third trimester was analyzed according to three criteria (early-onset, minimum of six consultations and puerperal consultation); and the compared maternal and perinatal outcomes were: type of childbirth, gestational age, birth weight and breastfeeding. The analysis was descriptive for the PHPN indicators and comparative for the prenatal adequacy by the chi-square test. Results: early prenatal (82.9%), minimum of six consultations (73.0%) and puerperal consultation (77.9%). In the overall of the PHPN indicators, there was an expressive decrease in the medical records (10.2%). Prenatal care was adequate for 63.6% with a significant difference in relation to gestational age (p=0.037) and birth weight (p=0.001). Conclusions: There were deficiencies in prenatal care. The difference between the groups in the perinatal outcomes reinforcing the need for prenatal care according to national indicators.